Nordic Prison Education : A Lifelong Learning Perspective - Langelid, Torfinn; Mäki, Marianne; Raundrup, Kaj; Svensson, Svenolov; S. Baldursson, Erlendur; Karsikas, Vuokko; Kuivajärvi, Kirsti (Copenhagen : Nordic Council of Ministers, 2009)
In 1999, the Nordic Council adopted a recommendation on prison education in a Nordic perspective. In September 2001, a Nordic project group was appointed to carry out a study, with representatives from the prison and probation services and the educational authorities. The project was directed by the County Governor of Hordaland, Norway. A decision was adopted in 2007 to revise the report in relation to recent research, new surveys, and general developments in the Nordic countries. The purpose of the project was to provide a concise, overall and updated comparative view of education and training in prisons in Denmark, Finland, Norway and Sweden, as well as a brief description of the situation in Iceland, Greenland, the Faeroe islands and the Åland islands. If convicted prisoners are to be offered education on equal terms with others in society, the right to education must be clearly stipulated in the legislation. According to this report, good cooperation between the prison and probation services and other authorities is one of the key starting points for satisfying prisoners' educational needs. The prison education offered today does not satisfactorily correspond to prisoners' educational needs. Increased investments in prison education would probably be of added value for society as a whole. This report provides useful documentation for individuals working with any aspect of the wider problem complex relating to prison and probation services.